Xijiao Dihuang Decoction combined with Yinqiao Powder reverses influenza virus-induced F-actin reorganization in PMVECs by inhibiting ERM phosphorylation - Xuan, Zinan (Journal of Traditional Chinese Medical Sciences, 2016)
OBJECTIVE: It has been documented that ezrin/radixin/moesin (ERM) phosphorylation by the p38 mitogen-activated protein kinase (MAPK), Rho/ROCK, and protein kinase C (PKC) pathways leads to filamentous actin (F-actin) reorganization and microvascular endothelial cell hyperpermeability. In this study, we investigated the effects of Xijiao Dihuang Decoction combined with Yinqiao Powder (XDY) on influenza virus (IV)-induced F-actin restructuring and ERM phosphorylation regulated by the Rho/Rho kinase 1 (ROCK), p38 MAPK, and PKC signaling pathways in pulmonary microvascular endothelial cells (PMVECs). METHODS: Serum containing XDY (XDY-CS; 13.8 g/kg) was acquired using standard protocols for serum pharmacology. Primary PMVECs were obtained from male Wistar rats and cultured. After adsorption of IV A (multiplicity of infection, 0.01) for 1 h, medium with 20% XDY-CS was added to the PMVECs. The distributions of F-actin and phosphorylated ERM were determined by confocal microscopy, and F-actin expression was measured by flow cytometry. The expression levels of ROCK1, phosphorylated myosin phosphatase target-subunit (p-MYPT), phosphorylated MAPK kinase, phosphorylated p38 (p-p38), phosphorylated PKC (p-PKC), and phosphorylated ERM (p-ERM) were determined by western blotting. RESULTS: F-actin reorganization in IV-infected PMVECs was reversed by XDY-CS treatment, which was accompanied by reduced p-ERM production. The p-ERM protein accumulated at plasma membrane of PMVECs infected with IV, which was also inhibited by XDY-CS treatment. In addition, XDY-CS treatment drastically reduced the levels of p-p38, ROCK1, p-MYPT, and p-PKC induced by IV infection in PMVECs. CONCLUSION: These results show that XDY-CS inhibited influenza-induced F-actin reorganization in PMVECs by down-regulating p-ERM expression via inhibition of the Rho/ROCK, p38 MAPK, and PKC pathways. In conclusion, XDY could reduce the damage to endothelial cytoskeleton induced by IV infection, thus protecting the barriers of PMVECs.